HIGH SCHOOL STUDENT COMPLAINT APPLICATION USING WEBSITE-BASED WATERFALL METHOD - Rifqi Ahmad Yurcel; Alisya Kayla Ramadhani; Putri Rehulina Br. Ginting; M. Dimas Raditia; Fatimah Azzahra (PT. Radja Intercontinental Publishing, 2025)
The web-based student complaint application aims to make complaint services more effective as a learning support and to make it easier for schools to respond to student complaints and aspirations regarding unsatisfactory school services. Previously, manual student complaints were considered ineffective due to the slow response received by students. The waterfall method in software development helps the process of running this application. Simplicity and ease of understanding are one of the main attractions, with an easy-to-understand linear structure. Each phase has clear stages with defined outcomes and a review process, ensuring clarity and understanding of requirements at the start of the project. This application effectively meets functional needs, especially in terms of ease of use for schools and students, and facilitates the automatic submission of complaints outside scheduled school hours.